2017
DOI: 10.1111/jav.01275
|View full text |Cite
|
Sign up to set email alerts
|

Opportunity costs influence food selection and giving‐up density of dabbling ducks

Abstract: The interaction of animals with their food can yield insights into habitat characteristics, such as perceived predation risk and relative quality. We deployed experimental foraging patches in wetlands used by migrating dabbling ducks Anas spp. in the central Illinois River Valley to estimate variation in seed removal and giving‐up density (GUD; i.e. density of food remaining in patches following abandonment) with respect to seed density, seed size, seed depth in the substrate, substrate firmness, perceived pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 44 publications
(91 reference statements)
0
21
0
1
Order By: Relevance
“…However, our observations were in contrast to the explanation provided by Legagneux et al (), who suggested that small roosting areas, low duck densities (<6.5 ducks/ha), and high resource availability led to shorter foraging flight distances than studies from North America. Waterbird and duck densities during autumn migration at large wetlands in our study area exceeded densities documented in France (Legagneux et al ; Hagy et al , ), and we posit that food and habitat availability were apparently abundant in portions of our study area outside of designated refuges (Stafford et al ; Hagy et al , ). Additionally, the landscape of central Illinois was dominated by agriculture and harvested crop fields were abundant during our study.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…However, our observations were in contrast to the explanation provided by Legagneux et al (), who suggested that small roosting areas, low duck densities (<6.5 ducks/ha), and high resource availability led to shorter foraging flight distances than studies from North America. Waterbird and duck densities during autumn migration at large wetlands in our study area exceeded densities documented in France (Legagneux et al ; Hagy et al , ), and we posit that food and habitat availability were apparently abundant in portions of our study area outside of designated refuges (Stafford et al ; Hagy et al , ). Additionally, the landscape of central Illinois was dominated by agriculture and harvested crop fields were abundant during our study.…”
Section: Discussionmentioning
confidence: 51%
“…Flooding and high river levels reduced wetland management capabilities and limited production of high‐quality moist‐soil vegetation in much of the Illinois River floodplain in both 2009 and 2010 that limited subsequent foraging habitat quality for ducks during autumn migration (Hagy et al ). In contrast, an unusually high water table in the central portion of our study area (i.e., Mason County) outside of the river floodplain in both years resulted in an abundance of privately owned wetlands in agricultural fields that likely were of high quality to dabbling ducks and received extensive use (Hagy et al ). Thus, foraging habitat quality on waterfowl refuges in the IRV was relatively low and ducks were likely forced to move to other areas, which could have exposed them to higher mortality during open hunting periods.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Throughout most of winter, open water, wooded, and aquatic bed wetlands likely provide less food energy to most species of dabbling ducks compared to moist‐soil wetlands, and primarily served other habitat functions (e.g., sanctuary, pair bonding, thermal cover). Conversely, food resources in moist‐soil and mudflat wetlands were apparently used during November through January until mean levels were likely too low to provide substantial energy to foraging birds (Hagy and Kaminski , Hagy et al ). Although densities of most species were greatest in moist soil where food densities were also greatest, this trend was inconsistent across other wetland types and patterns of habitat use and selection were likely influenced by many factors within our study area.…”
Section: Discussionmentioning
confidence: 99%
“…Gordon et al () and Cox and Afton () also observed associations between habitat use of dabbling ducks and the area of wetlands containing abundant foods. Research is limited that formally tests the hypothesis of food limitation on waterfowl during non‐breeding periods (Hagy and Kaminski , Hagy et al ). Food limitation during non‐breeding periods may reduce body condition and have carry‐over effects on subsequent survival and recruitment during the breeding season, but the relationship between waterfowl and food densities is complex (Hagy et al , Williams et al ).…”
Section: Discussionmentioning
confidence: 99%